Inhibitory Effects of Sodium Alginate on Hepatic Steatosis in Mice Induced by a Methionine- and Choline-Deficient Diet - Kawauchi, Shoji (Mar Drugs, 2019)
Nonalcoholic steatohepatitis (NASH) progresses from nonalcoholic fatty liver disease (NAFLD); however, efficacious drugs for NASH treatment are lacking. Sodium alginate (SA), a soluble dietary fiber extracted from brown algae, could protect the small intestine from enterobacterial invasion. NASH pathogenesis has been suggested to be associated with enterobacterial invasion, so we examined the effect of SA on methionine- and choline-deficient (MCD) diet-induced steatohepatitis in mice (the most widely-used model of NASH). The mice (n = 31) were divided into three groups (mice fed with regular chow, MCD diet, and MCD diet premixed with 5% SA) for 4 and 8 weeks. The MCD diet increased lipid accumulation and inflammation in the liver, the NAFLD Activity Score and hepatic mRNA expression of tumor necrosis factor-α and collagen 1α1, and induced macrophage infiltration. Villus shortening, disruption of zonula occludens-1 localization and depletion of mucus production were observed in the small intestine of the MCD-group mice. SA administration improved lipid accumulation and inflammation in the liver, and impaired barrier function in the small intestine. Collectively, these results suggest that SA is useful for NASH treatment because it can prevent hepatic inflammation and fatty degeneration by maintaining intestinal barrier function.